Discovering the Current Landscape of Liver Assessment through Viscosity and Shear Wave Elastography: State-of-the-Art Review - BAKKEN, SOFIA Maria; Serenari, Matteo; Fiorini, Giulia; Ruiz-Rodríguez, Jorge; Boccatonda, Andrea; Serra, Carla (Ultraschall in der Medizin - European Journal of Ultrasound)
Abstract (English Version) Ultrasound plays a central role in the diagnosis, monitoring, and management of liver diseases. Assessing hepatic fibrosis is essential in chronic liver disease, and several diagnostic modalities are available. The gold standard remains percutaneous liver biopsy, an invasive method using a 16–18-gauge needle. A breakthrough came in 2003 with transient elastography (TE), a noninvasive technique measuring liver stiffness (kPa) via elastic wave propagation. Later, shear wave elastography (SWE), integrated into modern ultrasound systems, was developed to assess tissue elasticity. SWE generates shear waves (SWs) through acoustic radiation force, assuming tissues to be linearly elastic and homogeneous, and provides quantitative stiffness data. Recent evidence shows hepatic tissue is viscoelastic, with wave propagation varying by frequency. Quantifying viscosity remains a challenge. Fibrosis affects viscoelastic properties and shear wave speed (SWS), while necroinflammation predominantly alters the viscous component, influencing shear wave dispersion slope (SWDS). This review provides an overview of ultrasound elastography, including stiffness and viscosity assessment, their physical principles, and clinical applications in hepatology. Abstract (German Version) Ultraschall ist zentral für Diagnose, Verlaufskontrolle und Therapie von Lebererkrankungen. Die Einschätzung des Fibrosegrads ist entscheidend im Management chronischer Lebererkrankungen. Goldstandard bleibt die invasive Leberbiopsie mit einer 16–18-Gauge-Nadel. Seit 2003 bietet die transiente Elastographie (TE) eine nichtinvasive Alternative, die die Lebersteifigkeit in kPa durch Messung elastischer Wellen bestimmt. Später wurde die Scherwellen-Elastographie (SWE) entwickelt, heute in moderne Ultraschallgeräte integriert. SWE erzeugt laterale Scherwellen (SWs) mittels akustischem Strahlungskraftimpuls und basiert auf der Annahme, dass Gewebe homogen und linear elastisch ist. Dies ermöglicht eine quantitative Bestimmung der Gewebesteifigkeit. Neuere Studien zeigen jedoch, dass Lebergewebe viskoelastisch ist – Wellen unterschiedlicher Frequenz breiten sich mit variabler Phasengeschwindigkeit aus. Die exakte Messung der Viskosität bleibt methodisch anspruchsvoll. Fibrose verändert viskoelastische Eigenschaften und die Scherwellen-Geschwindigkeit (SWS), während nekroinflammatorische Prozesse vor allem die viskose Komponente beeinflussen und damit den Scherwellen-Dispersions-Slope (SWDS). Diese Übersicht beleuchtet Elastographiemethoden zur Beurteilung von Steifigkeit und Viskosität, deren physikalische Grundlagen sowie klinische Anwendungen in der Hepatologie.